2015
DOI: 10.1159/000430145
|View full text |Cite
|
Sign up to set email alerts
|

Human Dental Pulp Stem Cells via the NF-κB Pathway

Abstract: Background/Aims: Odontogenic differentiation of human dental pulp stem cells (HDPSCs) is regulated by multiple factors and signaling molecules. However, their regulatory mechanisms are not completely understood. In this study, we investigated the role of Zinc finger and BTB domain-containing 20 (ZBTB20) in odontoblastic differentiation of HDPSCs. Methods: HDPSCs were obtained from human third molars and ZBTB20 expression was examined by qRT-PCR and western blot. Their osteo/odontogenic differentiation and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Approval for the whole research was obtained from the Ethics Committee of our hospital and the patients provided informed consent. DPSCs were isolated from dental pulp using the outgrowth method, and the cells were subsequently cultured in alpha-minimum essential medium (α-MEM; HyClone, Logan, UT, USA) containing 10% FBS according to a previous study [19, 20]. For DFO and iron treatment, DPSCs were incubated in culture medium containing different concentrations of DFO or DFO with ferric citrate (FC) at the indicated time.…”
Section: Methodsmentioning
confidence: 99%
“…Approval for the whole research was obtained from the Ethics Committee of our hospital and the patients provided informed consent. DPSCs were isolated from dental pulp using the outgrowth method, and the cells were subsequently cultured in alpha-minimum essential medium (α-MEM; HyClone, Logan, UT, USA) containing 10% FBS according to a previous study [19, 20]. For DFO and iron treatment, DPSCs were incubated in culture medium containing different concentrations of DFO or DFO with ferric citrate (FC) at the indicated time.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, selective targeting of NF-κB signaling could block the receptor activator for nuclear factor κB ligand (RANKL)-induced osteoclastogenesis and prevent osteoporotic bone destruction [19]. In addition, several researchers also demonstrated that estrogen deficiency activates NF-κB pathway, resulting in the inhibition of the odonto/osteogenic differentiation of dental pulp stem cells [20,21]. Thus, the wide involvement of NF-κB in skeletal remodeling and bone homeostasis makes it as a potential therapeutic target to inhibit bone resorption and promote bone formation.…”
mentioning
confidence: 99%
“…All patients gave their written informed consent to participate. DPSCs were obtained as described previously 21 . Cells were cultured in alpha‐minimum essential medium (a‐MEM; Hyclone, Logan, UT, USA) supplemented with 10% FBS, 100 U/mL penicillin, and 100 μg/mL streptomycin in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%